Analysis Of Factors Affecting Capital Structure (Empire Study On Lq45 Companies Listed On The Indonesia Stock Exchange) - Tiffany Natalia Petronela Gah (Enrichment : Journal of Management, 2022)
This study aims to see what factors affect the capital structure. This study uses secondary data related to LQ45 indexed companies listed on the Indonesia Stock Exchange in 2020-2021. The sample of this research is 40 companies indexed by LQ45 with purposive sampling method. The results of this study indicate that profitability, firm age, and firm size have no effect on capital structure and only liquidity has an effect on capital structure